Pengaruh Konsumsi Telur Rebus terhadap Penyembuhan Luka Post Sectio Caesarea pada Ibu Nifas di Rsud dr. Darsono Pacitan: The Effect of Boiled Egg Consumption on Post Sectio Caesarea Wound Healing in Postpartum Mothers at dr. Darsono Pacitan Hospital - Dian Tatariandari; Titik Kurniawati; Yustina Ananti (Journal of Health, 2024)
A sectio caesarea is a delivery in which the wall of the uterus is slashed surgically in order to deliver a fetus. The healing process for wounds is greatly influenced by nutrition, particularly protein. One of the most nutrient-dense foods, eggs are a type of animal protein side dish that are inexpensive, easy to find, and economical.This research is a quantitative research with quasy experimental method with a Nonequivalent group design. The research population is all caesarea postpartum mothers at dr. Darsono Pacitan Hospital. The sampling technique uses purposive sampling. The total sample was 36 post-SC postpartum mothers divided into two groups. Univariate data analysis with frequency distribution table, bivariate analysis with Chi-Square test. The duration of post sectio caesarea wound healing in postpartum mothers who consumed boiled eggs 18 mothers (100%) belonged to the category of fast healing (healed â‰¤ 7 days). The duration of post sectio caesarea wound healing in postpartum mothers who do not consume boiled eggs is dominated by mothers who belong to the category of slow healing wounds (healed > 7 days) as many as 10 mothers (55.6%). The Chiâ€“Square test result obtained the value Ï value = 0.000. Based on this figure, Ï < 0.05, there is an influence of boiled egg consumption on the healing of post sectio caesarea wounds in postpartum mothers at dr. Darsono Pacitan Hospital.